Síndrome de Fanconi e hepatocarcinoma por tirosinemia tipo 1: relato de caso e revisão de literatura - Maria Eduarda Turczyn De Lucca; Jhulia Farinha Maffini; Mariana Guerrini Grassi; Vinícius Neves Bezerra; Paulo Ramos David João; Mara Lúcia Schmitz Ferreira Santos; Sandra Lúcia Schuler (Residência Pediátrica, 2023)
INTRODUCTION: Type 1 tyrosinemia is an innate error of tyrosine catabolism, causing an accumulation of its metabolites in the organism, which end up triggering organic changes, especially in the liver, kidneys and central nervous system. CASE DESCRIPTION: Preschooler aged 4 years and 4 months, male, referred for suspicion of hypophosphatemic rickets. Hyperchloremic metabolic acidosis with normal anion gap, proteinuria and glycosuria was also identified, characterizing Fanconi syndrome. Abdominal ultrasound indicated enlarged liver and multiple hypoechoic nodular images. Tyrosinemia was placed as the main diagnostic hypothesis. Even without diagnostic conclusion, treatment with nitisone and diet with dietary restriction were initiated. After a short time, he died of complications from the disease. DISCUSSION: The severity of tyrosinemia is significant - and particularly its rapid evolution. However, it should be emphasized, the availability of effective diagnostic methods for the disease. In addition, there are currently treatments that allow a more favorable outcome. CONCLUSION: Thus, the need to transmit knowledge about this pathology is evident, so that the index of suspicion is high and early.